A GENETIC ALGORITHM FOR TWO DIMENSIONAL STRIP PACKING PROBLEMS - Mancapa, V; Van Niekerk, TI; Hua, T (The South African Journal of Industrial Engineering, 2009)
Cutting and packing problems are combinatorial optimisation problems. In most